The Issue of the Hurufism Prosecution and Edirne Case During the First Sultanate of Mehmed II (1444-1446) (Journal of Alevism-Bektashism Studies, 2023)
Hurufism is a philosophical and mystical thought movement systematized by Fazlullah Hurufi, who lived in the 14th century. Hurufism, which initially thrived in the Timurid State, later appeared in Khorasan, Anatolia and the Balkans. Hurufism has often been an elusive phenomenon, especially since the Hurufis preferred tooperate in secret, especially after the 15th century. Another reason is that Hurufism has a “mysterious language”. This difficulty is felt more especially in the case of Hurufis who lived in the Ottoman period. The fact that some poets and writers who are influenced by Hurufis more have themes evoking Hurufism, even if they are not Hurufis, increases this uncertainty. However, Hurufism thought is not as obscure as its history and is now widely known. It is noteworthy that after the Timurid State experience, Hurufis preferred to hide more in Anatolia and continued to exist by hiding in some cults, especially Bektashism. Hurufis also had a serious presence in Balkan regions such as Albania and Macedonia. When we look at the Works written by Hurufis and other historical records, it is sent hat the Hurufis deeply influenced the religious thought of the period. The first major problem that the Hurufis faced in Ottoman lands was a series of events that took place in Edirne around 1444. In these events, some Hurufi leaders who were close to Mehmed and many other Hurufis were executed. While these events took place in the atmosphere of political turmoil and under the threat of war in Edirne that year, it is worth examining whether these actions against the Hurufis have a relationship with the schism with in the Ottoman palace. In addition, some historians describe this event as a significant breaking point in the historical adventure of Hurufis. This breaking point also has determined the future attitude of the Hurufis. In this study, the relations the Hurufies established with II. Mehmed and the prosecutions they faced after wards examined within the framework of the historical atmosphere of the period. In addition, it has evaluated whether the events that took place in Edirne could be a Hurufi suprising or rebellion, and finally, the issue of how this process experienced by the Hurufis may have reflected on the in future attitudes discussed in the context of the relationship with Bektashism.